PENINGKATAN KOMPETENSI PENDIDIK ANAK USIA DINI DALAM MEMFASILITASI ANAK DENGAN KEBUTUHAN KHUSUS PADA SATUAN PENDIDIKAN INKLUSI - Patilima, Hamid; Rahayu, Tutin; Zakiyah, Lailatuz; Sugiarsih, Luluk; Gustini, Eti; Ekaningrum, Zulfi’a (LPPM Universitas Bina Bangsa, 2024)
The competence of educators in understanding inclusive education is very important, so Community Service (PKM) activities are needed with the theme